Microbiolization with Bacillus sp. in irrigated rice seed positively impacts physiological and phytosanitary quality - Souza , Wanessa; Oliveira , Liomar; Aguiar , Raimundo Wagner; Falcão, Daniel; Machado, Igor Eloi; Fidelis, Rodrigo (Revista de Ciencias Agrícolas, 2023)
Seed treatment is an important practice for reducing pathogens. The microbiolization technique has been used to provide economic and environmental benefits, starting with the selection of microorganisms and the identification of their mechanisms of action. In this sense, Bacillus sp. has stood out, having the capacity to promote growth and phytopathogenic control of several important crops such as rice. This study was conducted aiming to evaluate the protective effects of inoculation with six isolates of Bacillus sp. in rice seeds. Germination, germination speed index, shoot fresh weight, root fresh weight, seeding size, indoleacetic acid production, cellulase production, and antagonist phytosanitary analysis were evaluated. Our results revealed the best efficacy of isolate 47b in the tests of rice seed germination, root fresh weight, shoot fresh weight, seedling size, indoleacetic acid, and cellulase index. The 47b isolate, as it expressed better results in the previous tests, was subjected to different pHs, with pH 4, pH 6, and pH 8 being more efficient as a control measure (in the antagonism test) against Curvularia sp. This 47b isolate also performed very efficiently against Colletotrichum sp. at the pH4 and Macrophomina sp. at the pH 6. Our findings revealed the potential of the isolate 47b as a plant protectant against relevant phytopathogens and demonstrated its potential as a plant growth promoter.